2006
DOI: 10.1007/s10776-006-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traffic Distribution and Blocking Probability in Future Wireless Networks

Abstract: Future wireless networks are envisioned to provide good quality multimedia services to mobile users anywhere at anytime. Traditional analysis of teletraffic in such networks assumes that call arrivals follow a Poisson process, as each cell is being modeled as an M/G/c/c queueing system. This does not reflect the real situation since handoff traffic arrivals are not generally Poissonian. In this paper, we propose to model each cell in future wireless networks as a G/G/ c/c queueing system. As such a model has n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…To improve the performance of mobile cellular networks, a novel scheme is presented by Amin and Islam [1] by incorporating delay of voice end user to the new originating calls over handoff calls in a two dimensional traffic model. Beaubrun et al [2] presented a general model (i.e. G/G/c/c queueing system) for teletraffic analysis in future wireless networks and found that coefficient of variation of call arrivals has more impact on the network performance than coefficient of variation of channel holding time and the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To improve the performance of mobile cellular networks, a novel scheme is presented by Amin and Islam [1] by incorporating delay of voice end user to the new originating calls over handoff calls in a two dimensional traffic model. Beaubrun et al [2] presented a general model (i.e. G/G/c/c queueing system) for teletraffic analysis in future wireless networks and found that coefficient of variation of call arrivals has more impact on the network performance than coefficient of variation of channel holding time and the system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a wireless network, blocking occurs when a mobile terminal fails to obtain a free channel for initiating a service request [6]. In this context, the communication is blocked and cleared from the network.…”
Section: Introductionmentioning
confidence: 99%
“…It is being considered as an important design parameter for evaluating the level of quality of service (QoS) offered by a wireless network [4]. Its evaluation can be derived from a traffic model [6]. This paper proposes a method that takes into account the diversity and requirements of multimedia applications for evaluating blocking probabilities in multiservice wireless networks.…”
Section: Introductionmentioning
confidence: 99%
“…Several Queuing schemes incorporating FIFO queue have been proposed in literature [1][2][3]. These include priority and non priority schemes with corresponding importance reserved or denied for HO calls over new calls and also voice HO calls as compared to data HO calls.…”
Section: Introductionmentioning
confidence: 99%